Change in subfoveal choroidal thickness after argon laser panretinal photocoagulation - Cho, Ga Eun (International Journal of Ophthalmology Press, 2013)
AIM: To evaluate changes in subfoveal choroidal thickness (SFCT) and macular thickness as measured by enhanced depth imaging spectral-domain optical coherence tomography (EDI-OCT) after argon laser panretinal photocoagulation (PRP) in patients with severe diabetic retinopathy. METHODS: This prospective, comparative case series included 21 patients (28 eyes) with severe diabetic retinopathy. All patients underwent three sessions of PRP. The SFCT and macular thickness were measured using EDI-OCT at baseline and one week after completion of 3 sessions of PRP. RESULTS: SFCT before PRP was (318.1±96.5)µm and increased to (349.9±108.3)µm (P=0.001) after PRP. Macular thickness significantly increased at one week after PRP (from 273.1±23.9µm at baseline vs 295.8±25.3µm at one week; P<0.001). No significant relationship between the changes in macular thickness and SFCT was observed (r=-0.13, P=0.52). CONCLUSION: PRP induced increases in both SFCT and macular thickness. Changes in SFCT did not correlate with changes in macular thickness.